Biosolids from Wastewater Treatment Plant as an Alternative for Soil Decontamination with Aldrin Agrochemical - Andrea Del Pilar Gamarra Sánchez; Danny Lizarzaburu Aguinaga; Elmer Benites-Alfaro; Carlos Del Valle Jurado; Jorge Leonardo Jave Nakayo; Carlos Cabrera Carranza; Jorge López Bulnes; Guido Rene Suca Apaza (Chemical Engineering Transactions)
Soil contamination by agrochemicals is a significant environmental problem that can negatively impact human health, biodiversity, and water quality. Excessive or inappropriate use of agrochemicals, including the pesticide Aldrin, commonly used as an insecticide in agricultural activity, can contaminate soil. The research aimed to use biosolids from a wastewater treatment plant to decontaminate agricultural soil containing Aldrin pesticide. For the investigation, soil samples were taken from the Carabayllo area, and 2 kg were placed in each container; then, biosolids from the wastewater treatment plant were added in proportions of 10, 20, and 30 %, respectively. The test was done in triplicate for each percentage. After 90 days of treatment, a 70 % decrease in the pesticide Aldrin was found, for a rate of 30 % of biosolid added to the soil. Therefore, it is established that sewage biosolids allow the reduction of the pesticide Aldrin, becoming an environmentally sustainable alternative to decontaminate soils.